Effect of Social Media on Academic Performance of University Students in Nepal - Adhikari, Shreedhar (Academia Research Journal, 2024)
This study aims to explore the impact of social media on the academic performance of University students in Nepal. Through a comprehensive analysis of survey data and academic records, the research investigates the correlation between social media usage patterns and students’ grades. Factors such as frequency of social media engagement, types of platforms utilized, and time allocation for academic tasks are examined. The findings shed light on the nuanced relationship between social media activity and academic achievement, providing insights for educators, policy makers, and students in navigating the challenges posed by digital distractions in the academic setting.